In Stravinsky's Orbit Responses to Modernism in Russian Paris - Móricz, Klára (Academic Studies Press, 2022)
The Bolshevik's 1917 political coup caused a seismic disruption in Russian culture. Carried by the first wave of emigrants, Russian culture migrated West, where it was transformed by interactions with new cultural environment and clashed with exported Russian trends. In this book, Klára Móricz explores the transnational emigrant space of Russian composers Igor Stravinsky, Vladimir Dukelsky, Sergey Prokofiev, Nicolas Nabokov, and Arthur Lourié in interwar Paris. Their music reflected the conflict between a modernist narrative demanding innovation, and a narrative of exile wedded to the preservation of prerevolutionary Russian culture. The emigrants' and the Bolsheviks' contrasting visions of Russia and its past collided frequently in the French capital, where the Soviets displayed their political and artistic products. Russian composers in Paris also had to reckon with Stravinsky's disproportionate influence:if they succumbed to fashions dictated by their famous compatriot, they risked becoming epigones; if they kept to their old ways, they risked becoming irrelevant. Although Stravinsky's neoclassicism provided a seemingly neutral middle ground between innovation and nostalgia, it was also marked by the exilic experience. Móricz offers this unexplored context for Stravinsky's neoclassicism, shedding new light on this infinitely elusive term